From Sherbrooke to Stratford and back again: Team teaching and experiential learning through "Shakesperience". (April 2021) - Riddell, Jessica; Murray, Shannon; Dickson, Lisa
Attempting to teach theater in an English Literature course is a daunting prospect. A far cry from the highly individual experience of reading a novel or poem, theater is both a visual and communal kind of engagement. It is a challenge to capture this medium in a traditional lecture-based classroom and harder still to convey its three-dimensionality to undergraduate students. In this paper, we argue that experiential learning and team teaching are especially resonant in the exploration of Shakespearean studies because of the active and collaborative nature of his theater and plays. This paper draws out avenues for experiential learning in the humanities that should have broad applicability and interest a wide range of readers. Framing our design, implementation, and critical reflection in the relevant research, we provide an example of how to anchor experiential learning in the humanities in practice. The case study outlines a compact spring session course on Shakespeare's plays and performance that includes in-class, online, and field study components. Our research reveals that this approach mirrors in several key ways the collaborative work at the heart of Shakespearean drama and of theater more generally: students are exposed to the plays on the page, on the stage, and behind the scenes; they are offered a model of collaborative knowledge-making both in the theater and in the team-based course design and delivery; and, with these examples before them, they are encouraged to take risks, to collaborate, and to form communities of their own in their learning. In the conclusion we devote attention to funding and the cost associated with experiential learning and field courses. This paper explores experiential learning and field-based immersive learning into the context of disciplinary-specific humanities classrooms with the goal of increasing interaction among students and enhancing students' learning (Béchard and Pelletier, 2001 ).